Biodiversity beyond protected areas: Mammal responses to land-use and vegetation in a semi-arid mixed-use landscape - Maya Beukes; Travis Perry; Dan Parker; Otto Beukes; Nokubonga Mgqatsa (Biological Conservation, 2026)

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Forecasting the Risk of Brown Tree Snake Dispersal from Guam: a Mixed Transport‐Establishment Model - GAD PERRY; DAN VICE (Conservation Biology, 2009)
The brown tree snake ( Boiga irregularis ) is a devastating invader that has ecologically and economically affected Guam and is poised to disperse further. Interdiction efforts are being conducted on Guam and some of the potential receiving sites, but no tools exist for evaluating the potential for snake incursion; thus, the amount of effort that should be invested in protecting particular sites is unknown. We devised a model that predicts the relative risk of establishment of the brown tree snake (BTS) at a given site. To calculate overall risk, we incorporated in the model information on the likelihood of an organism entering the transportation system, avoiding detection, surviving to arrive at another location, and establishing at the receiving end. On the basis of documented rates of snake arrival at receiving sites, the model produced realistic predictions of invasion risk. Model outputs can thus be used to prioritize interdiction efforts to focus on especially vulnerable receiving locations. We provide examples of the utility of the model in evaluating the impacts of changes in transportation parameters. Finally, the model can be used to evaluate the impacts that BTS establishment at an additional site and that creation of a new source of snakes would have. The use of qualitative inputs allows the model to be adapted by substituting data on other invasive species or transportation systems.

Animal Rights and Conservation - Gad Perry; Dan Perry (Conservation Biology, 2008)

Improving Interactions between Animal Rights Groups and Conservation Biologists - DAN PERRY; GAD PERRY (Conservation Biology, 2008)
Invasive species are often considered to be a major threat to biodiversity, leading conservation biologists to often recommend their complete eradication. Animal rights groups typically categorically oppose killing animals, and their opposition has brought eradication attempts of gray squirrels in northern Italy (Europe) and mute swans in Vermont to a halt. As a result native red squirrels may disappear from Europe and ecosystem‐wide impacts are expected to be caused by the swan. In contrast, cooperation between managers and animal rights groups has resulted in a successful control program for feral pigs in Fort Worth, Texas (U.S.A.). The philosophical differences between animal rights and conservation biologists' views make cooperation seem unlikely, yet documented cases of cooperation have been beneficial for both groups. We recommend that managers dealing with invasive species should consult with social scientists and ethicists to gain a better understanding of the implications of some of their policy decisions. In addition, we recommend that animal rights groups do more to support alternatives to lethal control, which are often excluded by economic limitations. Prevention of arrival of invasive species via application of the precautionary principle may be an especially productive avenue for such collaboration because it fits the goals and values of both groups.